2019
DOI: 10.1002/mc.23130
|View full text |Cite
|
Sign up to set email alerts
|

ETV4 overexpression promotes progression of non–small cell lung cancer by upregulating PXN and MMP1 transcriptionally

Abstract: ETS variant 4 (ETV4), together with ETV1 and ETV5, constitute the PEA3 subfamily of ETS transcription factors, which are implicated in the progression of many cancers.However, the clinicopathologic significance and molecular events regulated by ETV4 in lung cancer are still poorly understood, especially in squamous cell carcinoma of the lung. Here, we aimed to identify functional targets involved in ETV4-driven lung tumorigenesis. Microarray analysis and validation data revealed that ETV4 was the most preponde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…Arraystar Human LncRNA Microarray V4.0 (Kangchen BioTech Co., Ltd.) was used to screen the global profiling of human lncRNAs and protein-coding transcripts. The samples included eight frozen tissues of NSCLCs (four samples of squamous cell carcinoma and four of adenocarcinoma) and paired normal lung tissues (GSE137445)(26). The total RNA was extracted from the cells or tissues as aforementioned.…”
mentioning
confidence: 99%
“…Arraystar Human LncRNA Microarray V4.0 (Kangchen BioTech Co., Ltd.) was used to screen the global profiling of human lncRNAs and protein-coding transcripts. The samples included eight frozen tissues of NSCLCs (four samples of squamous cell carcinoma and four of adenocarcinoma) and paired normal lung tissues (GSE137445)(26). The total RNA was extracted from the cells or tissues as aforementioned.…”
mentioning
confidence: 99%
“…Overexpression of ETV4 promotes progression, proliferation and invasion of many carcinomas. [ 43 , 69 , 70 ] STAT3 regulates glycolysis in hepatocellular carcinoma cells, [ 71 ] is associated with inhibition of epithelial-mesenchymal transition inhepatocellular carcinoma, [ 72 ] and is related to proliferation promotion and apoptosis inhibition in esophageal squamous cell carcinoma. [ 73 , 74 ] Previous studies have also identified a role for STAT3 in the regulation of PC.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ETV4 has been documented to be necessary for the activation of the estrogen signaling and proliferation of endometrial cancer cells (Rodriguez et al, 2020). As a transcription factor, it transcriptionally activated the paxillin (PXN) and matrix metalloproteinase 1 (MMP1) and promoted the progression of non–small cell lung cancer (Wang et al, 2020). Similar oncogenic mediations by ETV4 have been observed in malignancies, such as breast cancer (Dumortier et al, 2018), gastric cancer (Cai et al, 2020), and pancreatic cells (Tyagi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is well accepted that COAD is caused by genetic and epigenetic changes. ETS variant 4 (ETV4), ETV1, and ETV5 constitute the PEA3 subfamily of ETS transcription factors, which are frequently involved in the pathogenesis of many cancers (Wang et al, 2020). The PEA3 family factors are oncogenic transcription factors whose overexpression induces proliferation and invasiveness of cancer cells via triggering transcription of cell division‐ and migration‐related genes (Oh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%